Relasi Agama dan Negara: Kajian Teologi Politik Indonesia - Alfina Nur Lutfiah; Dadan Firdaus; Farid Nur Fauzan Naufal; Nisfah Nurfatihah; Sabda Maulana (INDO PUBLISHING, 2025)
Political theology is an academic approach that explores the relationship between theological thought religious views on God, humanity, and life and the political, social, and economic order. This field of study goes beyond the direct involvement of religion in politics, examining how divine values shape understandings of power, justice, and community life. This article specifically discusses the definition and scope of political theology in the Indonesian context—a nation that integrates religious principles with the national ideology of Pancasila. In Indonesia’s religiously and culturally plural society, political theology has emerged as a dynamic field of dialogue between religious teachings, democratic governance, and contemporary social realities. The article outlines how political theology can serve as both a reflective and critical tool for analyzing public policy, power distribution, and political morality. By elaborating on the core concepts of political theology and linking them to Indonesia’s sociopolitical landscape, this article aims to broaden the academic understanding of religion’s role in public life in a pluralistic nation.